1999
DOI: 10.1002/(sici)1097-0231(19990415)13:7<597::aid-rcm528>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-assisted laser desorption/Ionization coupled to Fourier transform ion cyclotron resonance mass spectrometry: a method to characterize temoporpfin photoproducts

Abstract: Photodynamic therapy (PDT) is a new rapidly developing method for cancer treatment, which is based on the systemic administration of a tumor-localizing photosensitizer (PS), followed by irradiation of the tumor with visible spectrally adapted light.1-3 The photochemical interaction of the PS, light and molecular oxygen results in the formation of singlet oxygen ( 1 O 2 ) and other reactive oxygen species (ROS), which are believed to be toxic species responsible for induction of tumor necrosis.2,3 5,10,15,20-m-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 18 publications
(24 reference statements)
1
16
0
Order By: Relevance
“…4). The ion at m / z 713.24 was attributed to the protonated dihydroxylated m ‐THPC ([ m ‐THPC + (O) 2 + H] + ) as has been described by several authors12, 29 and the ion at m / z 714.24 was attributed to dihydroxy m ‐THPBC ([ m ‐THPBC + (O) 2 ] +• ) due to a photo‐substitution mechanism. Two explanations can be proposed to clarify the nature of the ion at m / z 715.24: It could arise from the photo‐addition (photo‐hydratation) of the m ‐THPC, giving the protonated dihydro dihydroxy m ‐THPC noted on the figures [ m ‐THPC + (OH) 2 + H] + .…”
Section: Resultsmentioning
confidence: 99%
“…4). The ion at m / z 713.24 was attributed to the protonated dihydroxylated m ‐THPC ([ m ‐THPC + (O) 2 + H] + ) as has been described by several authors12, 29 and the ion at m / z 714.24 was attributed to dihydroxy m ‐THPBC ([ m ‐THPBC + (O) 2 ] +• ) due to a photo‐substitution mechanism. Two explanations can be proposed to clarify the nature of the ion at m / z 715.24: It could arise from the photo‐addition (photo‐hydratation) of the m ‐THPC, giving the protonated dihydro dihydroxy m ‐THPC noted on the figures [ m ‐THPC + (OH) 2 + H] + .…”
Section: Resultsmentioning
confidence: 99%
“…It is generally assumed that photodegradation of dyes such as PDT sensitizers can proceed via Type-I or singlet oxygen-mediated Type-II reactions (or both) (1), with one or the other predominating according to the sensitizer. In the solution phase, the relative contribution of the two mechanisms is also strongly dependent on the experimental conditions, such as the solvent used (32,33) or on the presence of biological substrates such as proteins. Therefore, some photoproducts detected, for example, in ethanolic solution of mTHPC (32) may not necessarily be generated in proteincontaining solution or in cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, some photoproducts detected, for example, in ethanolic solution of mTHPC (32) may not necessarily be generated in proteincontaining solution or in cells. Another aspect demonstrating the need for care when comparing solution phase results with cellular studies is the continuation of mTHPC degradation and product formation in the dark after irradiation, as reported for ethanolic solution (33). We did not observe any change of fluorescence intensity in the dark period after irradiation in the macrophage system.…”
Section: Discussionmentioning
confidence: 99%
“…Angotti et al. found evidence for both Type I and Type II reactions being involved in the photobleaching of m THPC (74) and identified m THPP as the primary photoproduct (75). Similar results were obtained using the HPLC separation of m THPC photoproducts after irradiation with 514 nm laser light in combination with MALDI‐TOF MS and UV/Vis spectroscopy.…”
Section: Chemistry and Development Of Temoporfinmentioning
confidence: 99%
“…A combined use of HPLC and electrospray ionization tandem MS (ESI-MS) identified mTHPP and several hydroxylated derivatives of both mTHPC and mTHPP as initial photobleaching products (73). Angotti et al found evidence for both Type I and Type II reactions being involved in the photobleaching of mTHPC (74) and identified mTHPP as the primary photoproduct (75). Similar results were obtained using the HPLC separation of mTHPC photoproducts after irradiation with 514 nm laser light in combination with MALDI-TOF MS and UV ⁄ Vis spectroscopy.…”
Section: Photobleachingmentioning
confidence: 99%